The nanostructure and mechanical properties of nanocomposite Nbx-CoCrCuFeNi thin films. (October 2017) - Braeckman, B.R.; Misják, F.; Radnóczi, G.; Caplovicová, M.; Djemia, Ph.; Tétard, F.; Belliard, L.; Depla, D.
Abstract: The relation between the nanostructure and the mechanical properties of Nbx -CoCrCuFeNi high entropy alloy thin films was explored. With increasing Nb concentration (0 to 24 at.% Nb), a transition from a single phase face-centered cubic solid solution to an amorphous phase is observed. At intermediary Nb fractions (5 to 15 at.% Nb) a nanocomposite structure is formed that consists of nanosized crystallites embedded in an amorphous matrix. The nanocomposite structure leads to an increase in hardness beyond the Hall-Petch breakdown. The shear and Young's moduli decrease with increasing Nb concentration, which is beneficial for the alloy ductility. Graphical abstract: